Implication of Future Time Perspective and Hope on the Continuance Commitment of Hotel Employees - Adrie Oktavio; Thomas Stefanus Kaihatu (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2020)
Abstract: In the Indonesian hotel industry, high employee turnover rates are very common costly. One of the reasons that causes hotel employee turnover to be high is low commitment. The low commitment is triggered by the low hope of hotel employees to remain and to be committed to continuing their careers in the hotel where they are working today. Employees need certainty about their future that should be guaranteed by hotel management. This study tries to analyze the role of Future Time Perspective (FTP) and its effect on hope and continuance commitment. The data were derived from distributing questionnaires to hotel employees spread in 45 three-star hotels in Surabaya, and subsequently analyzed using the General Structured Component Analysis (GSCA) tool. The results show that FTP influences hope and continuance commitment significantly. Similarly, hope has a significant effect on continuance commitment. Hope is also able to act as a mediator between FTP and continuance commitment.Keywords: hotel industry, future time perspective, hope, continuance commitment Implikasi Future Time Perspective dan Harapan Terhadap Continuance Commitment Karyawan HotelAbstrak: Di industri perhotelan Indonesia, tingkat turnover karyawan yang tinggi sudah menjadi rahasia umum dan sangat memakan biaya. Salah satu alasan yang menyebabkan tingginya tingkat turnover karyawan hotel adalah komitmen yang rendah. Komitmen yang rendah tersebut dipicu oleh rendahnya tingkat harapan karyawan hotel untuk tetap tinggal serta berkomitmen untuk melanjutkan karir di hotel tempat mereka bekerja saat ini. Karyawan hotel membutuhkan kepastian akan masa depannya yang seharusnya bisa dijamin oleh pihak manajemen hotel. Penelitian ini mencoba menganalisa peran Future Time perspective (FTP) dan pengaruhnya terhadap harapan dan continuance commitment karyawan hotel. Data penelitian berasal dari penyebaran kuesioner kepada karyawan hotel yang tersebar di 45 hotel bintang tiga di Surabaya dan selanjutnya dianalisis menggunakan alat analisis General Structured Component Analysis (GSCA). Hasilnya menunjukkan bahwa FTP mempengaruhi harapan dan continuance commitment secara signifikan. Harapan juga berpengaruh secara signifikan terhadap continuance commitment. Harapan juga berperan sebagai mediator antara FTP dan continuance commitment.Kata kunci: industri perhotelan, future time perspective, harapan, continuance commitment